The turbulence in the Norwegian money market in autumn 2022 - Inga-Malene Huse; Joakim Johnsen Pettersen; Ingebjørg Hansen Sævareid (Norges Bank, 2023)
Record-high payments of petroleum tax in October 2022, and the accompanying fall in structural liquidity, resulted in a marked rise in the shortest-term Norwegian money market rates. In this staff memo we describe how petroleum tax payments affect liquidity in the banking system and discuss why money market rates increased considerably, even though Norges Bank offered a number of F-loans to banks. Data from Norges Bank's money market reporting (RPD) show that it was foreign banks lacking access to Norges Bank's market operations that borrowed NOK at very high interest rates in the FX swap market. Regulatory requirements and internal guidelines relating to liquidity and capital adequacy limited the amount banks could borrow from Norges Bank and constituted an important factor behind the rise in money market rates.
hdl:11250/3166361
Keywords: 330